The influence of beekeeping products on the health of the population of the Republic of Moldova (One Health & Risk Management, 2021)
Introduction. Honey is a semi-liquid substance, with a sweet taste and pleasant aroma, rich in sugars and vitamins, produced by bees from the nectar of flowers, as well as from sweet tree secretions that they yield and remove from the outside. Bees produce a multitude of products that are rich in many bioactive compounds, such as propolis, pollen, honey, royal jelly and bee venom. Due to the high nutrient content of most bee products, these have begun to be consumed as food supplements over the recent decades.According to the classification, bee products can be classified into primary and secondary ones. Primary bee products include honey, wax and pollen. The bee by-products are royal jelly, propolis and pasture. Numerous researches have also been carried out on the potential of bee products as agents in the cure of cancer, neurodegenerative diseases, cardiovascular diseases, gastrointestinal tract, as well as for the treatment of wounds and burns.The purpose of the study. To study the influence of bee products on the health of the population of the Republic of Moldova, as well as their use in the treatment of various diseases.Material and methods. The systematic analysis of the specialized literature was performed by using the appropriate methods and tools relevant to the proposed purpose.The study was conducted on 76 people (aged between 19 and 32 years) from the Republic of Moldova. The research was conducted during the 2020-2021.Results. A total number of 76 responses were obtained and received evaluated, with a sex distribution ratio of 1: 1. 86.8% of the respondents answered that they know about the benefits of bee products, while 84.2% confirmed the consumption of bee products. The most consumed bee products are as follows: honey (94.3%), propolis (37.1%) and honeycombs (28.6%). 47.4% of respondents consume bee products occasionally, 31.6% – weekly and 13.2% – daily. Raw honey is used in 45% of cases, which is the recommended method of consumption. Most respondents (39.5%) consume a recommended amount of honey of 10-12 g per day (50-100 g per week). 21.1% consume more than 100 g per week. And 34.2% consume less than 15 g per week. No one mentioned that they do not consume bee products due to allergies or pathologies and for whom honey consumption might be a contraindication. This study showed that most population consumes bee products and recognizes the nutritional and curative value of these products.Conclusions. Due to their specific properties, bee products have a binomial value, i.e. they simultaneously fulfill the function of food and medicine. They not only heal, but also nourish and bring the necessary energy intake. Despite technological developments, honey is the only product in the world that could not be artificially synthesized. This fact further emphasizes its curative value and implicitly the importance of the existence of bees. Following the questionnaire, the most commonly consumed bee product remains honey, which de facto has the most beneficial effects on health.
Keywords: honey; bees; beekeeping; health.